Multivariate optimization of Selaginellae Herba carbonization processing and its comparative analysis of antioxidant activity between crude and processed products - Wenting Zhong; Xi Wang; Hui Wang; Feng Gao; Menghua Wu; Zhiguo Ma; Tulin Lu; Hui Cao; Ying Zhang (Journal of Agriculture and Food Research)
Objective: To optimize Selaginellae Herba Carbonisata (SH-Ca) processing using Box-Behnken Design Response Surface Methodology (BBD-RSM) combined with Analytic Hierarchy Process (AHP) and Entropy Weight Method (EWM), and comparatively evaluate its antioxidant enhancement over crude herb (SH-Cr) Methods: Processing parameters (input quantity, temperature, time) were optimized via BBD-RSM-AHP-EWM, with quality assessed by carbon adsorption capacity (CAC), total flavonoid content (TFC), chromatic aberration value (CAV), and appearance characteristics scoring (ACS). Additionally, the antioxidant capacities of SH-Cr and SH-Ca were evaluated using the DPPH radical scavenging activity, OH radical scavenging activity, ABTS-based total antioxidant capacity (T-AOC), and FRAP-based T-AOC assays. Results: AHP and EWM were applied to assign appropriate weights to these indicators, with ACS (58.27 %) being the most critical parameter, followed by TFC (24.33 %), CAV (13.54 %), and ACS (3.86 %). Model validation confirmed that the optimized conditions (an input quantity of 28 g, a temperature of 315 ± 15 °C, a processing time of 9.5 min) produced consistent results. While SH-Cr showed superior DPPH radical scavenging at high concentrations, SH-Ca exhibited more stable but generally lower scavenging activity across all tested concentrations. In contrast, SH-Ca displayed significantly enhanced OH radical scavenging activity (P < 0.05) and FRAP-based T-AOC compared to SH-Cr (P < 0.05), with its most notable advantage in ABTS-based T-AOC (P < 0.05) at high concentrations. Conclusion: The integrated BBD-RSM-AHP-EWM approach enabled optimal processing of SH-Ca, with comparative analysis revealing that SH-Ca exhibited superior efficacy against radical-induced oxidative damage whereas SH-Cr showed stronger direct radical quenching capacity. These findings provide insights for developing natural antioxidants with customized properties.